Rural-urban inequities in childhood immunisation in Nigeria: The role of community contexts - Diddy Antai (AOSIS, 2011)
Context: Childhood vaccinations are one of the most cost-effective means of reducing negative child health outcomes. Despite the benefits of immunisation, inequities persist both between and within rural-urban areas in Nigeria. Objectives: To assess the role of community contexts on rural-urban inequities in full immunisation uptake amongst children 12 months of age and older. Methods: Data from the 2003 Nigeria Demographic and Health Survey including 6029 live born children from 3725 women aged 15-49 years were examined using multilevel regression analysis. Results: Rural children were disadvantaged both in the proportion receiving full immunisation and individual vaccines. Contextual or community-level factors such as community prenatal care by doctor, community hospital delivery, and region of residence accounted for significant rural-urban inequities in full immunisation. Conclusion: This study stresses the need for community-level interventions aimed at closing rural-urban inequities in the provision of maternal and child health care services.